Proccedings of 10th International Conference "Environmental Engineering" 2017
DOI: 10.3846/enviro.2017.153
|View full text |Cite
|
Sign up to set email alerts
|

Review of Lithuanian Experience in Asphalt Pavements Cold Recycling

Abstract: One of the key goals in the EU White Paper is to reduce carbon emissions in transport by 60% by 2050. Consequently, during the past years an effect on the environment became a decisive factor in selecting materials and technologies for road construction and rehabilitation. Cold recycling is a reasonable solution in asphalt pavement rehabilitation because it is economical and old asphalt pavements can be reused. This technology differs from others by mixing temperature. Besides, cold recycling does not require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, only a few studies have attempted to investigate the bearing capacity of pavement structures with a cold-recycled base course, despite the significantly increasing usage of cold-recycled mixtures. Vaitkus et al [16] summarized the results from the plate load test on a cold-recycled base course in nine different road sections and concluded that mixtures bound with both a bituminous emulsion and cement have a higher bearing capacity than those with foamed bitumen and cement. Meocci et al [17] analyzed measurements from a falling weight deflectometer (FWD) on the cold recycled base course after 29 days and 90 days of curing.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have attempted to investigate the bearing capacity of pavement structures with a cold-recycled base course, despite the significantly increasing usage of cold-recycled mixtures. Vaitkus et al [16] summarized the results from the plate load test on a cold-recycled base course in nine different road sections and concluded that mixtures bound with both a bituminous emulsion and cement have a higher bearing capacity than those with foamed bitumen and cement. Meocci et al [17] analyzed measurements from a falling weight deflectometer (FWD) on the cold recycled base course after 29 days and 90 days of curing.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches on the performance of cold recycled mixtures has been done (Babagoli et al, 2016;Betti et al, 2016;Bocci et al, 2011;Dal Ben & Jenkins, 2014;Iwański & Chomicz-Kowalska, 2011Leandri et al, 2015;Mueller et al, 2014;Niazi & Jalili, 2009 Vaitkus et al, 2017;Yan et al, 2017). However, there is unclear how the performance of the entire pavement structure (cold recycled asphalt pavement overlaid with asphalt mixture) depends on the binding agent.…”
Section: Introductionmentioning
confidence: 99%
“…New materials require the study of the peculiarities of their performance in a temperature-time field in order to develop objective technical requirements for their physical and mechanical properties, which ensure the required strength and reliability values. In addition to the authors, the issues of obtaining and optimizing the composition and structure of OHB concrete are dealt with by experts in most countries of the world [1][2][3][4][5][6]. The main technological parameters for concrete production have been established, studies of composition effect on strength have been carried out, and in-use life has been examined [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%